Loneliness among elderly in nursing homes - Aung, Khin Thandar; Nurumal, Mohd. Said; Wan Bukhari, Wan Nur Syakirah (2017)
Elderly is very vulnerable to loneliness and it is a barrier to achieve successful ageing. Prevalence of loneliness among the elderly is increasing as well as other associated factors that make it worse. in addition, loneliness has a negative impact on our quality of life, and mental and physical health. Moreover, the assessment and identification of loneliness among the elderly are slightly ignored by the health care providers. There is no specific tool to measure the level of loneliness among elderly in Malaysia health care settings. Moreover, by measuring the loneliness level for elderly will help them and health care providers to demonstrate the positive impact of their work on the way people feel about their relationships and connections. The aim of this study was to explore the level of loneliness among elderly in nursing homes using UCLA loneliness scale.A quantitative crosssectional design conducted in nine nursing homes chosen by a stratified random sampling method in Kuantan, Pahang, Malaysia.Eighty elderly was involved and self-modified questionnaire for sociodemographic data and UCLA loneliness scale that was used to measure the level of loneliness with internal consistency (coefficient α ranging from 0.89 to 0.94) and test-retest reliability (r = 0.73).The descriptive analysis, such as frequency and percentage and Chi-Square test was analyzed using the (SPSS) version 20. 75% of elderly felt very high loneliness while 25% felt moderately loneliness. These participants were mostly came from age-group 71-80s, female, Chinese, not schooling, already loss spouse and don’t have any jobs currently. About 58.8% suffered illnesses and 62.5% faced physical limitation. However, the overall result indicates that there was no association between socio-demographic factors and level of loneliness, but all elderly experienced loneliness either moderately or very high.Early detection and lonely screening are the first stage of primary prevention for elderly. It is very advisable to apply a simple tool, UCLA Loneliness Scale to measure the level of loneliness. For the health care providers, they can provide the best facilities and health services for elderly in helping to reach good quality of life as well as successful aging along their life journey.